Eksplorasi literatur tentang risiko reputasi di bank syariah: Faktor, dampak, dan strategi pengelolaan - Setiawan, Aldika Bayu (Maliki Interdisciplinary Journal, 2025)
Reputational risk is a crucial aspect for Islamic banks, considering that their operations are not only based on profitability but also on moral integrity and compliance with sharia principles. This article conducts a literature exploration to comprehensively identify the causative factors, impacts, and reputation risk management strategies that are relevant for Islamic banks. Through a systematic literature review, this research synthesizes previous studies. The findings show that the drivers of reputational risk include non-compliance with Shariah principles, operational issues such as fraud and system weaknesses, weak corporate governance including lack of transparency and passive role of the Shariah Supervisory Board (DPS), negative impact of media and rumors in the digital era, and ineffective crisis communication. The impact of this risk is very significant, including a decrease in customer and investor trust leading to withdrawal risk, financial losses, brand damage, decreased loyalty, difficulty in expansion, and potential threats to the stability and sustainability of Islamic banks, even the industry as a whole. Effective management strategies involve strengthening sharia compliance through the active role of DPS and sharia audit, improving corporate governance and information transparency (including Shariah Social Reporting), solid operational risk management, and developing a responsive crisis management and crisis communication system that is in line with Islamic values. This study underlines that reputation risk management is a fundamental strategic element to maintain the integrity, trust, and sustainability of Islamic banks amidst the challenges of the financial services industry.